2023
DOI: 10.5114/aoms/160941
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of ferroptosis in myocardial fibrosis of atrial fibrillation

Abstract: IntroductionThe aim of this study was to investigate the relationship between ferroptosis and myocardial fibrosis in atrial fibrillation (AF).Material and methodsThe patient’s left atrial appendage tissue was obtained in cardiac surgery. Sirius red staining, Prussian blue and Western blot were used to detect staining to assess histological fibrosis and ferroptosis changes.ResultsThere is a certain correlation between the degree of tissue fibrosis and ferroptosis in AF (r = 0.7763, p = 0.0004). The key proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Ferroptosis is involved in myocardial fibrosis and several studies have investigated the relationship between ferroptosis and myocardial fibrosis. [ 17 ] Acot1 knockdown increases oxidative stress and inflammation and most likely results in fibrosis. [ 7 ] Researchers have proposed that LOX may play a role in a small proportion of cases of ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis is involved in myocardial fibrosis and several studies have investigated the relationship between ferroptosis and myocardial fibrosis. [ 17 ] Acot1 knockdown increases oxidative stress and inflammation and most likely results in fibrosis. [ 7 ] Researchers have proposed that LOX may play a role in a small proportion of cases of ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exploration of ferroptosis’s connection with AF remains relatively uncharted territory. At present, it has been shown that AF is associated with ferroptosis, including the bioactive molecules related to ferroptosis [ 36 ]. Therefore, a multi-dimensional analysis of ferroptosis in the context of AF is imperative.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed a notable association between cardiomyocyte fibrosis and ferroptosis in patients with AF, with findings indicating a higher incidence of fibrosis in this group compared to controls [ 36 ]. The specific mechanisms linking atrial myocyte fibrosis and AF to ferroptosis, as well as the role of inflammation in this process, remain underexplored.…”
Section: The Role Of Ferroptosis and Inflammation In Afmentioning
confidence: 99%
See 1 more Smart Citation
“…Yue et al . [ 27 ] analyzed samples of left ear tissue from patients suffering from persistent AF, and detected significantly higher iron particle levels in these samples via Prussian blue staining consistent with the AF-related dysregulation of iron metabolism. In line with these results, Rose et al .…”
Section: The Molecular and Metabolic Processes Between Ferroptosis An...mentioning
confidence: 96%